#TITLE_ALTERNATIVE# - RAHMAN (NIM: 12304022), ANDRIO
Common seismic methods were used in seismic processing, such as NMO stack and DMO stack are usually processed using CMP method, and known as conventional methods. CDP fold in small amount in seismic data couldn't be processed by conventional methods to obtain seismic secion with high to noise ratio. In recent years, Common Reflection Surface (CRS) method is used to correct the CMP method and could produce a better quality of seismic section than conventional methods. In this study, the CRS method is used to obtain seismic stack section with high noise to ratio in the case study seismic data with small CDP fold. The study was specified in two main stages: seismic data processing using conventional methods and using CRS method. Software ProMAX is used in seismic data processing to obtain CRS stack section and CRS gathers which could show better subsurface imaging than conventional methods. After poststack miration, migrated CRS stack could representative the real geologic setting and could help geology interpretation.